Help-seeking behavior of individuals with schizophrenia in the general population of Hunan, China - Jiawen Hu (Nature Portfolio, 2021)
Abstract This study aims to know the seeking help behavior of individuals with SZ (Schizophrenia) in Hunan province of China. Individuals (age > 15) with schizophrenia were recruited in the study after a two-stage diagnosis procedure (including questionnaire screening and face-to-face SCID interview by psychiatrists) in Hunan province. A self-designed questionnaire was used to investigate their help-seeking behavior. (1) Of the 367 participants, 68.9% (253/367) sought help; of those, 64.6% (n = 163) pursued professional psychiatric services and 30.8% (n = 78) pursued non-medical options (i.e., relatives, praying to Buddha) as the most common first choices. (2) Family history of mental disorders is significantly related to whether or not the individual with SZ seeks help, and the first choice of help is significantly related to education level. (P < 0.05). (3) Frequent reasons behind not seeking help include fear of stigmatization (72.9%), poor mental health literacy (64.5%), concerns over cost (50.6%), and limited access to medical services (47.0%). About one-third of the individuals do not seek help. Individuals with SZ tend to choose psychiatric hospitals and relatives as their first choice. Among the factors we investigated, family history of mental disorders is the most influential factor associated with help-seeking behavior. Individuals with more education tend to seek professional help first. The primary reasons for not seeking help include fear of stigmatization, lack of awareness about mental illness, concerns over cost, etc.